Retrospective Approach to the Endemic Dianthus fruticosus L. ssp. fruticosus on Serifos Island (Cyclades, Greece) - Sophia Rhizopoulou; John Pouris (Plants, 2024)
The carnation Dianthus fruticosus L. ssp. fruticosus (Caryophyllaceae) is a range-restricted perennial, endemic plant that grows on cliffs, rocks, ravines, terraces, and boulders on Serifos Island in the Cyclades in the Aegean archipelago (Greece), possessing an impressive, aesthetic blossoming during the dry season. This indigenous carnation of Serifos has attracted the interest of naturalists and scientists. Specimens of this subspecific taxon from the island of Serifos (Greece) were collected during botanical explorations in preindustrial times by the French naturalist Joseph Pitton de Tournefort (1702) and in the late eighteenth century by the English Professor of Botany at the University of Oxford John Sibthorp (1787). Those specimens, documented in relevant publications and labelled with different names (i.e., Caryophyllus Graecus arboreus and Caryophyllus arboreus Seriphius in the early eighteenth century and Dianthus fruticosus in the early nineteenth century), are related to aspects of vegetation history, linking the past to the present and (most probably) to the future. Today, a thorough understanding of the in situ development and functionality of this endemic carnation is still required, as is a framework of its sustainability and management in small-scale insular habitats. The timeless perception of the emblematic wild carnation Dianthus fruticosus ssp. fruticosus, which is still growing on inland and coastal sites of Serifos and neighboring islands in the Cyclades (Greece), is also a reminder that a native plant is often a repository to which local communities may look when crafting their identity.